PENGARUH LITERASI NUMERASI DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Monalisa; Ismah; Muhamad Sofian Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low ability of numeracy literacy, learning motivation, and critical thinking skills of elementary school students, which is a problem in the 21st century. The purpose of this research is (1) to test the influence between numeracy literacy and learning motivation with critical thinking skills of Mathematics of Grade IV Elementary School students in Cipedak Village, (2) to test the influence between numeracy literacy with critical thinking skills of Mathematics of Grade IV Elementary School students in Cipedak Village, and (3) to test the influence between learning motivation with critical thinking skills of Mathematics of Grade IV Elementary School students in Cipedak Village The type of research used is quantitative survey research. The population in this study were fourth grade students from 3 public elementary schools in Cipedak Village with a sample size of 183 students. The instruments used were questionnaires and tests. The results of the study showed that the critical thinking skills of fourth grade elementary school students in Cipedak Village were still low with the results of the Two Way ANOVA test showing that numeracy literacy had a significant effect on students' critical thinking skills in mathematics (F = 12.098; p < 0.001), which indicates that students with better numeracy literacy tend to have higher critical thinking skills. In addition, learning motivation also had a significant effect on critical thinking skills (F = 3.185; p = 0.044), although the effect was smaller than numeracy literacy. Furthermore, the study found a significant interaction between numeracy literacy and learning motivation on critical thinking skills in mathematics (F = 6.394; p = 0.002). This finding indicates that students' critical thinking skills will develop optimally if good numeracy literacy is supported by strong learning motivation. Overall, the research model was able to explain approximately 24% of the variation in critical thinking skills, while the remainder was influenced by factors other than the research variables.